PENGARUH DIGITAL MARKETING MENGGUNAKAN SOSIAL MEDIA TERHADAP PENGEMBANGAN SEKTOR EKONOMI DESA SEMPA JAYA KABUPATEN KARO - Muhammad Rizki Lubis (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2022)
Digitizing the tourism industry is one of the right steps in responding to digital-oriented society civilization in meeting their needs for traveling. One of the efforts in realizing the digitization of tourism is the use of ICT (Information and Communication Technology). The purpose of this study was to determine the effect of digital marketing using social media on the development of the economic sector in Sempa Jaya Village, Karo Regency. The research was conducted in Sempa Jaya Village, Karo Regency in May 2022. The research method used in this study was descriptive quantitative research. Sampling was done by purposive sampling. The data analysis technique used is simple regression analysis. Based on the results of data analysis and discussion, it can be concluded that digital marketing has a positive and significant effect on the economic sector of Sempa Jaya village, Karo Regency. The higher the level of digital marketing, the economic sector of the tourist village will also be improved.